Histochemical and Immunohistochemical Studies on Pig Spleen (Sus scrofa) - Kaur, Harmanpreet; Singh, Opinder; Pathak, Devendra (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Histochemical and immunohistochemical studies were conducted on spleen of 12 healthy and normal pigs. The sections were stained with various stains to study the histochemical details. The capsule and trabeculae showed moderate activity for neutral and acid mucopolysaccharides and proteins whereas white pulp showed weak activity for acidic mucopolysaccharides and moderate to strong for neutral mucopolysaccharides. The lymphocytes present in lymphoid follicle of white pulp and erythrocytes in sinuses were devoid of acid mucopolysaccharides activity but periphery showed positive reaction. The ellipsoids and lymphocytes in germinal centre showed weakly positive activity. The capsule and trabeculae showed positive reaction for phospholipids and bromophenol blue positive activity was observed throughout the spleen. Polymer based horseradish peroxidase method was used to demonstrate the presence of B-lymphocyte and T-lymphocyte in white pulp. Localization of more T-lymphocytes and macrophages in white pulp and ellipsoids implied that T-lymphocytes possibly act as major phagocytic cell in spleen.